Visual Identity Kue Browqies sebagai Media Promosi di Kota Malang - Mayangsari, Pinky Diah; Hendrawan, Faldi (Jurnal Desain Komunikasi Visual Asia, 2022)
ABSTRACT Browqies are brownies topped with melted chocolate on top. Browqies is a cake with a soft and dense texture, dark brown in color and has a distinctive chocolate taste. However, for many years this product has not been known by consumers. It turns out that this is due to the lack of media promotion built by the browqies product. The solution offered in this research is the design of Visual Identity as a promotional medium for the Browqies Cake product. Where visual identity is a visual communication system that forms the identity/personality of a company, institution, or product. The results of testing with alternative methods of filling out questionnaires in this study showed that out of ten buyers who agreed with the Visual Identity design, they were able to provide a value of trust and attract consumers to buy products with packaging, and promotional media such as posters, flyers, x-banners and media. namely merchandise. Keywords: Visual Identity, Browqies Malang City.